International Marketing and Export Management - Albaum, Gerald; Duerr, Edwin; Strandskov, Jesper; Josiassen, Alexander; Polonsky, Michael (Pearson International Content, 2016)
International Marketing and Export Management offers an accessible text in international marketing. The book covers the evolving internationally competitive landscape that almost all firms and consumers find themselves acting in today. Consumers because they often make consumption choices where there are international options, and firms because they either compete internationally or have international competitors in their domestic market.   The edition retains its clear and comprehensive coverage of the opportunities for companies of all sizes and in all industries in the export of goods, services, intellectual property and business models. The full text downloaded to your computer With eBooks you can: search for key concepts, words and phrases make highlights and notes as you study share your notes with friends eBooks are downloaded to your computer and accessible either offline through the Bookshelf (available as a free download), available online and also via the iPad and Android apps. Upon purchase, you'll gain instant access to this eBook. Time limit The eBooks products do not have an expiry date. You will continue to access your digital ebook products whilst you have your Bookshelf installed.